Synthesis of sodium zincsilicate (Na2ZnSiO4) and heterogeneous catalysis towards biodiesel production via Box-Behnken design. (15th November 2020) - Rodríguez-Ramírez, R.; Romero-Ibarra, I.; Vazquez-Arenas, J.
Highlights: Synthesis of Na2 ZnSiO4 via a facile and low-cost solid-state method. Na2 ZnSiO4 evaluated as heterogeneous catalysts in soybean oil transesterification. Transesterification reaction parameters optimized using Box-Behnken design. 99% FAMEs conversion achieved under optimized conditions at 65 °C after 45 min. Optimized conditions using 5.3 wt% catalyst, 500 RPM and 1:14 MeOH:oil ratio. Abstract: This study synthesizes a Na2 ZnSiO4 phase as efficient and low-cost heterogeneous catalyst for biodiesel production. X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) along with Energy Dispersive X-Ray Spectroscopy (EDS), Brunauer–Emmett–Teller (BET) surface area analysis isotherms are herein conducted to characterize the structure, texture, composition and surface area of the catalyst, respectively. A Box-Behnken design (BBD) is performed to screen out: the methanol: oil ratio (6:1 to 14:1), catalyst load (0.5 to 5.5 wt%) and stirring rate (500 to 800 RPM), affecting the transesterification reaction using commercial soybean oil as a triglyceride source while fixing the temperature reaction at 65 °C. The oil and its fatty acid methyl esters (FAME) are characterized using Fourier Transform Infrared Spectroscopy with an Attenuated Total Reflectance modulus (FT-IR-ATR). XRD and SEM confirm the successful synthesis of the monoclinic Na2 ZnSiO4 phase with low traces of ZnO (<5 wt%) and undetectable for Na2 SiO3 ; presenting a BET surface area around 1.9 m 2 g −1 . The material is quite active towards the biodiesel production since a conversion superior to 99% is achieved in 45 min, using the statistical optimization conditions estimated with the BBD, 500 RPM, 5.30 wt% and 14:1 MeOH: Oil ratio. According to the response surface methodology, the sensitivity of the parameters increases in the following order: catalyst load > methanol: oil ratio > stirring rate. The FAME conversions drop to 48.4 and 62.42% after 5 cycles of continuous catalyst reuse, according to FT-IR-ATR and proton nuclear magnetic resonance ( 1 H NMR) measurements, respectively.